Non-aqueous electrolyte and secondary battery
Patent Information
- Application Number
- JP2023516336
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-23
- Filing Date
- 2022-03-14
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2042-03-14
AI Technical Summary
【0011】 本開示によれば、スルホニルイミド化合物を含む非水電解液において、電池性能の改善を図ることが可能な非水電解液、当該非水電解液を備えた二次電池を提供することができる。
Smart Images

Figure 0007627335000001 
Figure 0007627335000002 
Figure 0007627335000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a nonaqueous electrolyte and a secondary battery. [Background technology]
[0002] In order to improve the battery performance of secondary batteries such as lithium ion secondary batteries, various nonaqueous electrolyte solutions for use in secondary batteries have been studied. For example, Patent Document 1 proposes a nonaqueous electrolyte solution containing an electrolyte including a lithium-containing complex compound. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2019 / 180945 Summary of the Invention [Problem to be solved by the invention]
[0004] Meanwhile, the present inventors have found through their investigations that a non-aqueous electrolyte solution containing a sulfonylimide compound such as lithium bis(fluorosulfonyl)imide as an electrolyte improves the battery performance, such as high-temperature durability and charge / discharge cycle performance, of a lithium ion secondary battery.
[0005] However, Patent Document 1 does not consider a non-aqueous electrolyte solution containing a sulfonylimide compound.
[0006] The present disclosure has been made in consideration of the above points, and an object of the present disclosure is to provide a nonaqueous electrolyte solution containing a sulfonylimide compound that can improve battery performance, and a secondary battery including the nonaqueous electrolyte solution. [Means for solving the problem]
[0007] As a result of further investigation, the present inventors have found that a battery using a non-aqueous electrolyte solution containing a sulfonylimide compound can be used with a lithium compound other than the sulfonylimide compound (e.g., LiPF 6 , LiBF 4 It has been found that compared with a battery using a nonaqueous electrolyte containing only a sulfonylimide compound (lithium bis(fluorosulfonyl)imide, etc.), the self-discharge from a fully charged state is large, and there is room for improvement in the storage characteristics of the battery. This finding was first discovered by the present inventors, and neither Patent Document 1 nor other documents mention the self-discharge of a battery using a nonaqueous electrolyte containing a sulfonylimide compound (particularly lithium bis(fluorosulfonyl)imide).
[0008] In order to improve the storage characteristics and battery performance of the above-mentioned battery, the disclosed technology is designed to suppress the self-discharge of the battery, which is a specific problem, in a non-aqueous electrolyte solution containing a sulfonylimide compound, and also to improve the charging characteristics at low temperatures.
[0009] The nonaqueous electrolyte of the present disclosure is General formula (1): LiN(R 1 SO 2 )(R 2 SO 2 ) (1) (In formula (1), R 1 and R 2 are the same or different and represent a fluorine atom, an alkyl group having 1 to 6 carbon atoms, or a fluoroalkyl group having 1 to 6 carbon atoms.) A compound represented by the formula: General formula (2): LiPF a (C m F 2m+1 ) 6-a (2) (In formula (2), a: 0≦a≦6, m: 1≦m≦4.) A compound represented by the formula: General formula (3):(Li) m (A) n (U.F. x ) y (3) In formula (3), A represents an oxygen atom, a sulfur atom, a phosphorus atom, or a nitrogen atom, and U represents a boron atom or a phosphorus atom. m: 1≦m≦6, n: 1≦ n ≦6, x: 3 or 5, y: 1≦y≦6. In the non-aqueous electrolyte, the compound represented by the general formula (3) is (LiBF 3 ) 2 O and LiBF 3 The compound represented by the general formula (1) may contain at least one of LiN(FSO 2 ) 2 The molar ratio of the concentration of the compound represented by the general formula (1) to the concentration of the compound represented by the general formula (2) may be 1:25 or more and 5:1 or less, 1:120 or more and 1:25 or less, 5:1 or more and 12:1 or less, or 1:120 or more and 12:1 or less. The nonaqueous electrolyte may further contain a fluorine-containing carbonate compound.
[0010] The secondary battery of the present disclosure uses the nonaqueous electrolyte. The secondary battery may include a separator having at least one surface coated with inorganic particles. Effect of the Invention
[0011] According to the present disclosure, it is possible to provide a nonaqueous electrolyte solution containing a sulfonylimide compound that can improve battery performance, and a secondary battery including the nonaqueous electrolyte solution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present embodiment will be described in detail below with reference to the drawings. The following description of the preferred embodiment is merely illustrative in nature and is not intended to limit the present invention, its application, or its uses.
[0013] <Nonaqueous electrolyte> The non-aqueous electrolyte according to this embodiment contains the compounds represented by the general formulas (1) to (3). That is, this non-aqueous electrolyte contains the compounds represented by the general formulas (1) to (3) as essential components.
[0014] (Compound represented by general formula (1)) The compound represented by the general formula (1) is represented by the general formula (1): [C1] LiN(R 1 SO 2 )(R 2 SO 2 ) (1) (hereinafter referred to as “sulfonylimide compound (1)”, a fluorine-containing sulfonylimide salt) represented by the formula:
[0015] In general formula (1), R 1 and R 2 are the same or different (independently of each other) and represent a fluorine atom, an alkyl group having 1 to 6 carbon atoms, or a fluoroalkyl group having 1 to 6 carbon atoms.
[0016] Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a pentyl group, and a hexyl group. Among the alkyl groups having 1 to 6 carbon atoms, a linear or branched alkyl group having 1 to 6 carbon atoms is preferred, and a linear alkyl group having 1 to 6 carbon atoms is more preferred.
[0017] Examples of the fluoroalkyl group having 1 to 6 carbon atoms include an alkyl group having 1 to 6 carbon atoms in which some or all of the hydrogen atoms have been substituted with fluorine atoms. Examples of the fluoroalkyl group having 1 to 6 carbon atoms include a fluoromethyl group, a difluoromethyl group, a trifluoromethyl group, a fluoroethyl group, a difluoroethyl group, a trifluoroethyl group, and a pentafluoroethyl group. In particular, the fluoroalkyl group may be a perfluoroalkyl group.
[0018] Substituent R 1 and R 2As the substituent R, a fluorine atom and a perfluoroalkyl group (for example, a perfluoroalkyl group having 1 to 6 carbon atoms, such as a trifluoromethyl group, a pentafluoroethyl group, a heptafluoropropyl group, etc.) are preferable, a fluorine atom, a trifluoromethyl group, and a pentafluoroethyl group are more preferable, a fluorine atom and a trifluoromethyl group are even more preferable, and a fluorine atom is even more preferable. 1 and R 2 may be the same or different from each other.
[0019] The sulfonylimide compound (1) is, for example, lithium bis(fluorosulfonyl)imide (LiN(FSO 2 ) 2 , hereinafter referred to as "LiFSI"), lithium bis(trifluoromethylsulfonyl)imide (LiN(CF 3 SO 2 ) 2 , hereinafter also referred to as "LiTFSI"), lithium (fluorosulfonyl) (methylsulfonyl) imide, lithium (fluorosulfonyl) (ethylsulfonyl) imide, lithium (fluorosulfonyl) (trifluoromethylsulfonyl) imide, lithium (fluorosulfonyl) (pentafluoroethylsulfonyl) imide, lithium (fluorosulfonyl) (heptafluoropropylsulfonyl) imide, lithium bis (pentafluoroethylsulfonyl) imide, lithium bis (heptafluoropropylsulfonyl) imide, etc. The sulfonylimide compound (1) may be used alone or in combination of two or more kinds. The sulfonylimide compound (1) may be a commercially available product, or may be obtained by synthesis by a conventionally known method.
[0020] Among the sulfonylimide compounds (1), LiN(FSO 2 ) 2 and LiN(CF 3 SO 2 ) 2 is preferred, and LiN(FSO 2 ) 2In other words, in the non-aqueous electrolyte, the sulfonylimide compound (1) is more preferably LiN(FSO 2 ) 2 and LiN(CF 3 SO 2 ) 2 It is preferable to use LiN(FSO 2 ) 2 It is more preferable that the sulfonylimide compound (1) is present (contained) in the non-aqueous electrolyte in the form of ions.
[0021] (Compound represented by general formula (2)) The compound represented by the general formula (2) is represented by the general formula (2): [Case 2] LiPF a (C m F 2m+1 ) 6-a (2) (hereinafter referred to as “fluorophosphate compound (2)”) represented by the following formula:
[0022] In the general formula (2), a: 0≦a≦6, and m: 1≦m≦4.
[0023] The fluorophosphate compound (2) is LiPF 6 , LiPF 3 (CF 3 ) 3 , LiPF 3 (C 2 F 5 ) 3 , LiPF 3 (C 3 F 7 ) 3 , LiPF 3 (C 4 F 9 ) 3 The fluorophosphate compound (2) may be used alone or in combination of two or more kinds. The fluorophosphate compound (2) may be a commercially available product or may be synthesized by a conventional method.
[0024] Among the fluorophosphate compounds (2), LiPF 6 and LiPF 3 (C 2 F 5 ) 3 is preferred, LiPF 6 The fluorophosphate compound (2) may be present (contained) in the non-aqueous electrolyte in the form of ions.
[0025] (Compound represented by general formula (3)) The compound represented by general formula (3) is represented by general formula (3): [C3] (Li) m (A) n (U.F. x ) y (3) (hereinafter referred to as “complex compound (3)”) represented by the following formula:
[0026] In the general formula (3), A represents an oxygen atom (O), a sulfur atom (S), a phosphorus atom (P) or a nitrogen atom (N). Among A, from the viewpoints of the stability of the lithium salt, solubility in a solvent, etc., an oxygen atom and a sulfur atom are preferred, and an oxygen atom is more preferred.
[0027] In the general formula (3), U represents a boron atom (B) or a phosphorus atom (P). Among U, a boron atom is preferred from the viewpoint of bonding with A (particularly an oxygen atom, a sulfur atom, or a nitrogen atom).
[0028] In general formula (3), m:1≦m≦6, n:1≦ n ≦6, x: 3 or 5, y: 1≦y≦6. m and n are the same or different (independently of each other), and preferably 1≦m≦3, more preferably 1 or 2. x is preferably 3 from the viewpoint of solubility in the electrolyte solvent. y is preferably 1≦ y < 3 is preferred.
[0029] The complex compound (3) is, for example, O-(BF 3 Li)(Li) (Note: O-(BF 3Li)(Li) is Li-O(-BF 3 - Li + The compounds exemplified below are also complexes having the same structure as above. Hereinafter, "LiBF 3 OLi], O-(BF 3 Li) 2 [Hereinafter referred to as “(LiBF 3 ) 2 O". 〕, S-(BF 3 Li)(Li), S-(BF 3 Li) 2 , N-(BF 3 Li) 2 (Li), N-(BF 3 Li) 3 , P-(BF 3 Li) 2 (Li), P-(BF 3 Li) 3 , O-(PF 5 Li)(Li), O-(PF 5 Li) 2 , S-(PF 5 Li)(Li), S-(PF 5 Li) 2 , N-(PF 5 Li) 3 The complex compound (3) may be used alone or in combination of two or more. The complex compound (3) may be a commercially available product or may be synthesized by a conventional method.
[0030] Among the complex compounds (3), LiBF is the most suitable from the viewpoints of stability and solubility in solvents of the complex compound (3). 3 OLi, (LiBF 3 ) 2 O,S-(BF 3 Li)(Li), S-(BF 3 Li) 2 , N-(BF 3 Li) 3 , P-(BF 3 Li) 3 , O-(PF 5 Li)(Li), O-(PF 5 Li) 2, S-(PF 5 Li)(Li), S-(PF 5 Li) 2 and N-(PF 5 Li) 3 is preferred, and LiBF 3 OLi and (LiBF 3 ) 2 O is more preferable. In other words, in the nonaqueous electrolyte, the complex compound (3) is LiBF 3 OLi and (LiBF 3 ) 2 Preferably, the compound contains at least one of O.
[0031] The concentration of the sulfonylimide compound (1) in the non-aqueous electrolyte is preferably 0.01 mol / L or more, more preferably 0.05 mol / L or more, even more preferably 0.1 mol / L or more, even more preferably 0.3 mol / L or more, and even more preferably 0.5 mol / L or more, from the viewpoint of improving the charging characteristics at low temperatures. Also, the concentration is preferably 5 mol / L or less, more preferably 3 mol / L or less, even more preferably 2 mol / L or less, even more preferably 1.5 mol / L or less, and even more preferably 1 mol / L or less, from the viewpoint of suppressing the deterioration of the battery performance due to the increase in the electrolyte viscosity and improving the charging characteristics at low temperatures.
[0032] The concentration of the fluorophosphate compound (2) in the nonaqueous electrolyte is preferably 0.1 mol / L or more, more preferably 0.2 mol / L or more, even more preferably 0.3 mol / L or more, and even more preferably 0.5 mol / L or more, from the viewpoint of improving the charging characteristics at low temperatures. Also, from the viewpoint of improving the charging characteristics at low temperatures, the concentration is preferably 1.5 mol / L or less, more preferably 1 mol / L or less, and even more preferably 0.8 mol / L or less.
[0033] The total concentration of the sulfonylimide compound (1) and the fluorophosphate compound (2) is preferably 0.8 mol / L or more, more preferably 1 mol / L or more, even more preferably 1.1 mol / L or more, and even more preferably 1.2 mol / L or more from the viewpoint of improving the charging characteristics at low temperatures. Moreover, the concentration is preferably 5 mol / L or less, more preferably 3 mol / L or less, even more preferably 2.5 mol / L or less, even more preferably 2.3 mol / L or less, even more preferably 2 mol / L or less, and particularly preferably 1.5 mol / L or less from the viewpoint of suppressing the deterioration of the battery performance due to the increase in the electrolyte viscosity and improving the charging characteristics at low temperatures.
[0034] From the viewpoint of improving the charging characteristics at low temperatures, it is preferable to increase the concentration of the sulfonylimide compound (1). The molar ratio of the sulfonylimide compound (1) to the fluorophosphate compound (2) (the molar ratio of the sulfonylimide compound (1) concentration to the fluorophosphate compound (2) concentration) is preferably 1:25 or more, more preferably 1:10 or more, even more preferably 1:8 or more, even more preferably 1:5 or more, even more preferably 1:2 or more, and particularly preferably 1:1 or more. The upper limit is preferably 5:1 or less, more preferably 4:1 or less, even more preferably 3:1 or less, and even more preferably 2:1 or less.
[0035] The molar ratio is not limited to the above range, and the effect of improving the charging characteristics at low temperatures can be obtained even in a range wider than the range. Specifically, the molar ratio of sulfonylimide compound (1) to fluorophosphate compound (2) (the molar ratio of the sulfonylimide compound (1) concentration to the fluorophosphate compound (2) concentration) may be 1:120 or more, 1:100 or more, 1:50 or more, 12:1 or less, 10:1 or less, or 8:1 or less. For example, the molar ratio may be 1:120 or more and 1:25 or less (less than), 5:1 or more (excessive) and 12:1 or less, or in the broadest range, 1:120 or more and 12:1 or less.
[0036] The content (addition amount) of the complex compound (3) in the non-aqueous electrolyte is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and even more preferably 0.5% by mass or more, based on 100% by mass of the non-aqueous electrolyte, from the viewpoint of improving the charging characteristics at low temperatures and suppressing self-discharge. The upper limit is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, even more preferably 3% by mass or less, and even more preferably 2% by mass or less.
[0037] Thus, the nonaqueous electrolyte according to the present embodiment includes the compounds (1) to (3), and the combination of the specific three components improves the charging characteristics at low temperatures, and also suppresses self-discharge, which is a problem specific to nonaqueous electrolytes containing the sulfonylimide compound (1), particularly self-discharge after high-temperature storage. Note that a battery using a nonaqueous electrolyte containing only the two components of the sulfonylimide compound (1) and the complex compound (3), without containing the fluorophosphate compound (2), cannot be charged normally and cannot operate as a battery. This finding was also discovered by the present inventors. In other words, the nonaqueous electrolyte according to the present embodiment can solve the above problems collectively by using the compounds (1) to (3) in combination, and a synergistic effect of improving the charging characteristics and storage characteristics can be obtained.
[0038] (Other Ingredients) The nonaqueous electrolyte solution according to the present embodiment may contain, in addition to the compounds (1) to (3), imide salts and non-imide salts that are generally used as electrolytes, and additives for improving various characteristics of lithium ion secondary batteries.
[0039] Examples of the imide salt include other fluorine-containing sulfonylimide salts (hereinafter referred to as "other sulfonylimide compounds") different from the sulfonylimide compound (1). Examples of the other sulfonylimide compounds include non-lithium salts of the fluorine-containing sulfonylimides listed as the sulfonylimide compound (1) (for example, salts in which lithium (ion) in the sulfonylimide compound (1) is replaced with a cation other than lithium ion). Examples of salts in which a cation other than lithium ion is replaced include alkali metal salts such as sodium salts, potassium salts, rubidium salts, and cesium salts; alkaline earth metal salts such as beryllium salts, magnesium salts, calcium salts, strontium salts, and barium salts; aluminum salts; ammonium salts; and phosphonium salts. The other sulfonylimide compounds may be used alone or in combination of two or more kinds. The other sulfonylimide compounds may be commercially available products or may be synthesized by a conventional method. The other sulfonylimide compounds may be present (contained) in the form of ions in the nonaqueous electrolyte.
[0040] Examples of the non-imide salt include salts of non-imide anions and cations (lithium ions and the above-listed cations). Examples of the non-imide salt include LiBF 4 , LiBF(CF 3 ) 3 , LiBF(C 2 F 5 ) 3 , LiBF(C 3 F 7 ) 3 , lithium hexafluoroarsenate (LiAsF 6 ), LiSbF 6 , LiClO 4 , LiSCN, LiAlF 4 , C.F. 3 SO 3 Li, LiC[(CF 3 SO 2 ) 3 ], LiN(NO 2 ), LiN[(CN) 2Lithium salts such as those mentioned above; non-lithium salts (for example, salts in which the lithium (ion) in these lithium salts is replaced with the above-mentioned cations (for example, NaBF 4 , NaPF 6 , NaPF 3 (CF 3 ) 3 The non-imide salts may be used alone or in combination of two or more. The non-imide salts may be commercially available products or may be synthesized by a conventional method. The non-imide salts may be present (contained) in the form of ions in the non-aqueous electrolyte.
[0041] Additives include carboxylic acid anhydrides such as succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, diglycolic anhydride, cyclohexanedicarboxylic anhydride, cyclopentanetetracarboxylic dianhydride, and phenylsuccinic anhydride; sulfur-containing compounds such as ethylene sulfite, 1,3-propane sultone, 1,4-butane sultone, methyl methanesulfonate, busulfan, sulfolane, sulfolene, dimethyl sulfone, tetramethylthiuram monosulfide, and trimethylene glycol sulfate; 1-methyl-2-pyrrolidinone, 1-methyl -2-piperidone, 3-methyl-2-oxazolidinone, 1,3-dimethyl-2-imidazolidinone, N-methylsuccinimide, and other nitrogen-containing compounds; heptane, octane, cycloheptane, and other saturated hydrocarbon compounds; phenylethylene carbonate, erythritan carbonate, and other carbonate compounds; fluoroethylene carbonate (FEC), 4,5-difluoroethylene carbonate, trifluoropropylene carbonate, bis(trifluoromethyl)carbonate, ethyl(trifluoromethyl)carbonate, and other fluorine-containing carbonate compounds; sulfamic acid (amidosulfuric acid, H 3 NSO 3);sulfamates (alkali metal salts such as lithium salts, sodium salts, potassium salts, etc.; alkaline earth metal salts such as calcium salts, strontium salts, barium salts, etc.; other metal salts such as manganese salts, copper salts, zinc salts, iron salts, cobalt salts, nickel salts, etc.; ammonium salts; guanidine salts, etc.); lithium monofluorophosphate (Li 2 PO 3 F), lithium difluorophosphate (LiPO 2 F 2 Fluorophosphate compounds such as lithium fluorosulfonate (LiFSO 3 ), sodium fluorosulfonate (NaFSO 3 ), potassium fluorosulfonate (KFSO 3 ), magnesium fluorosulfonate (Mg(FSO 3 ) 2 Fluorosulfonic acid compounds such as lithium bis(oxalato)borate (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium difluorooxalatophosphanite (LIDFOP), lithium tetrafluorooxalatophosphate (LITFOP), lithium difluorobis(oxalato)phosphate (LiDFOP), lithium tris(oxalato)phosphate, and the like; and lithium salts having an oxalic acid skeleton such as lithium tris(oxalato)phosphate. These additives may be used alone or in combination of two or more. Among these additives, from the viewpoint of further improving the synergistic effect of the combination of the compounds (1) to (3), fluorine-containing carbonate compounds are preferred, and fluoroethylene carbonate (FEC) is more preferred.
[0042] The content (addition amount) of the additive in the non-aqueous electrolyte is preferably 0.1% by mass or more and 25% by mass or less, more preferably 0.5% by mass or more and 15% by mass or less, even more preferably 3% by mass or more and 15% by mass or less, and even more preferably 5% by mass or more and 10% by mass or less, based on 100% by mass of the non-aqueous electrolyte. If the amount of the other additive used is too small, it may be difficult to obtain the effect derived from the other additive, while if a large amount of the other additive is used, it is difficult to obtain the effect corresponding to the amount added, and the viscosity of the non-aqueous electrolyte may increase, resulting in a decrease in conductivity.
[0043] (Electrolyte Solvent) The non-aqueous electrolyte according to the present embodiment may contain an electrolyte solvent. The electrolyte solvent is not particularly limited as long as it can dissolve and disperse the above-mentioned compounds (1) to (3) and other components. Examples of the electrolyte solvent include non-aqueous solvents, and media such as polymers and polymer gels used in place of electrolyte solvents. Any solvent generally used in batteries can be used.
[0044] The non-aqueous solvent is preferably a solvent having a large dielectric constant, high solubility for the electrolyte salt, a boiling point of 60° C. or higher, and a wide electrochemical stability range, and more preferably an organic solvent having a low water content. Examples of such organic solvents include ether solvents such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 2,6-dimethyltetrahydrofuran, tetrahydropyran, crown ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,4-dioxane, and 1,3-dioxolane; chain carbonate ester (carbonate) solvents such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, diphenyl carbonate, and methyl phenyl carbonate; saturated cyclic carbonate ester solvents such as ethylene carbonate, propylene carbonate, 2,3-dimethyl ethylene carbonate, 1,2-butylene carbonate, and erythritan carbonate; cyclic carbonate ester solvents having an unsaturated bond such as vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, 2-vinyl ethylene carbonate, and phenyl ethylene carbonate; methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, methyl propionate, ethyl propionate, propionate, Aliphatic carboxylate solvents such as propyl propionate, butyl acetate, and isopropyl propionate; aromatic carboxylate solvents such as methyl benzoate and ethyl benzoate; lactone solvents such as γ-butyrolactone, γ-valerolactone, and δ-valerolactone; phosphate solvents such as trimethyl phosphate, ethyl dimethyl phosphate, diethyl methyl phosphate, and triethyl phosphate; acetonitrile, propionitrile, methoxypropionitrile, glutaronitrile, adiponitrile, 2-methylglutaronitrile, Examples of suitable solvents include nitrile solvents such as nitrile, valeronitrile, butyronitrile, and isobutyronitrile; sulfur compound solvents such as dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, sulfolane, 3-methyl sulfolane, and 2,4-dimethyl sulfolane; aromatic nitrile solvents such as benzonitrile and tolunitrile; nitromethane, 1,3-dimethyl-2-imidazolidinone, 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone, and 3-methyl-2-oxazolidinone.These solvents may be used alone or in combination of two or more kinds.
[0045] Among the electrolyte solvents, carbonate solvents such as chain carbonate ester solvents and cyclic carbonate ester solvents, lactone solvents, and ether solvents are preferred, with dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, γ-butyrolactone, γ-valerolactone, and the like being more preferred, and carbonate solvents such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethylene carbonate, and propylene carbonate being even more preferred.
[0046] When a polymer or polymer gel is used instead of the electrolyte solvent, the following methods may be adopted: a method of dropping a solution of an electrolyte salt dissolved in a solvent onto a polymer film formed by a conventionally known method, thereby impregnating and supporting the electrolyte salt and the non-aqueous solvent; a method of melting and mixing a polymer and an electrolyte salt at a temperature equal to or higher than the melting point of the polymer, forming a film, and impregnating the film with the solvent (the above are referred to as gel electrolyte); a method of mixing a non-aqueous electrolyte solution in which an electrolyte salt has been dissolved in an organic solvent with a polymer, forming a film by a casting method or a coating method, and volatilizing the organic solvent; a method of melting a polymer and an electrolyte salt at a temperature equal to or higher than the melting point of the polymer, mixing them, and forming them (true polymer electrolyte); and the like.
[0047] Examples of polymers that can be used in place of the electrolyte solvent include polyethylene oxide (PEO), which is a homopolymer or copolymer of epoxy compounds (ethylene oxide, propylene oxide, butylene oxide, allyl glycidyl ether, etc.), polyether-based polymers such as polypropylene oxide, methacrylic polymers such as polymethyl methacrylate (PMMA), nitrile-based polymers such as polyacrylonitrile (PAN), fluorine-based polymers such as polyvinylidene fluoride (PVdF) and polyvinylidene fluoride-hexafluoropropylene, and copolymers thereof. These polymers may be used alone or in combination of two or more.
[0048] The nonaqueous electrolyte thus constructed is used, for example, in batteries (batteries having a charge / discharge mechanism), electricity storage (electrochemical) devices (or ion conductor materials constituting these), etc. Specifically, the electrolyte can be used as an electrolyte constituting, for example, primary batteries, secondary batteries (for example, lithium (ion) secondary batteries), fuel cells, electrolytic capacitors, electric double layer capacitors, solar cells, electrochromic display elements, etc. Hereinafter, an explanation will be given taking batteries (particularly secondary batteries) as an example.
[0049] <Secondary battery> The secondary battery according to this embodiment includes a positive electrode, a negative electrode, and a nonaqueous electrolyte. In this secondary battery, the nonaqueous electrolyte according to this embodiment, that is, the nonaqueous electrolyte containing the compounds (1) to (3) as essential components, is used as the nonaqueous electrolyte.
[0050] (positive electrode) The positive electrode includes a positive electrode current collector and a positive electrode mixture layer, and the positive electrode mixture layer is formed on the positive electrode current collector and is usually formed into a sheet shape.
[0051] Examples of metals used for the positive electrode current collector include iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. Among these, aluminum is preferred. The shape and dimensions of the positive electrode current collector are not particularly limited.
[0052] The positive electrode mixture layer is formed of a positive electrode mixture (positive electrode composition) that contains a positive electrode active material, a conductive assistant, a binder, a solvent for dispersing these components, and the like.
[0053] In the secondary battery according to this embodiment, the positive electrode (positive electrode mixture) is preferably LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 , LiNi 0.5 Co 0.2 Mn 0.3 O 2 , LiNi 0.6 Co 0.2 Mn 0.2 O 2 , LiNi0.8 Co 0.1 Mn 0.1 O 2 Ternary positive electrode active materials such as LiFePO 4 , Life 0.995 Mn 0.005 PO 4 The positive electrode active materials may be preferably used as iron phosphate-based positive electrode active materials having an olivine structure, such as: These positive electrode active materials may be used alone, or two or more of them may be used in combination.
[0054] The positive electrode preferably contains at least one of the above-mentioned ternary positive electrode active material and iron phosphate positive electrode active material, but may contain other positive electrode active materials. The other positive electrode active materials may be any materials capable of absorbing and releasing various ions (lithium ions, sodium ions, etc.), and may be, for example, positive electrode active materials used in conventionally known secondary batteries (lithium ion secondary batteries, sodium ion secondary batteries), etc.
[0055] Positive electrode active materials used in lithium ion secondary batteries include, for example, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, LiNi 1-v-w Co x Al y O 2 (0≦v≦1, 0≦w≦1) other than the above-mentioned ternary oxides of the positive electrode active material; LiAPO 4 Compounds with an olivine structure such as (A = Mn, Ni, Co); solid-solution materials incorporating multiple transition metals (electrochemically inactive layered Li 2 MnO 3 and electrochemically active layered LiMO 2 (M = Co, Ni, etc.) solid solution); LiCo x Mn 1-x O 2 (0≦x≦1); LiNi x Mn 1-x O 2 (0≦x≦1);Li 2 APO 4Compounds having a fluorinated olivine structure such as F (A=Fe, Mn, Ni, Co) and the like; sulfur, etc. can be used. These may be used alone or in combination of two or more kinds.
[0056] The positive electrode active material used in sodium ion secondary batteries is, for example, NaNiO 2 , NaCoO 2 , NaMnO 2 , NaVO 2 , NaFeO 2 , Na(Ni X Mn 1-X )O 2 (0 <X<1)、Na(Fe X Mn 1-X )O 2 (0 <X<1)、NaVPO 4 F, Na 2 FePO 4 F, Na 3 V 2 (PO 4 ) 3 These may be used alone or in combination of two or more kinds.
[0057] Among other positive electrode active materials, a positive electrode active material capable of absorbing and releasing lithium ions may be preferably used. Such a positive electrode active material is used, for example, in a lithium ion secondary battery using a non-aqueous electrolyte. Such a non-aqueous electrolyte usually has a lower ion conductivity than an aqueous electrolyte, but the present disclosure can efficiently improve the discharge capacity even in such a case.
[0058] From the viewpoint of improving the output characteristics and electrical characteristics of the secondary battery, the content of the positive electrode active material (the total content when multiple positive electrode active materials are included) is preferably 75 mass % or more, more preferably 85 mass % or more, and even more preferably 90 mass % or more, relative to 100 mass % of the total amount of the components contained in the positive electrode composite, and is preferably 99 mass % or less, more preferably 98 mass % or less, and even more preferably 95 mass % or less.
[0059] The conductive assistant is used to improve the output of the lithium ion secondary battery. As the conductive assistant, conductive carbon is mainly used. Examples of conductive carbon include carbon black, fibrous carbon, and graphite. The conductive assistant may be used alone or in combination of two or more kinds. Among the conductive assistants, carbon black is preferable. Examples of carbon black include ketjen black and acetylene black. The content of the conductive assistant in the non-volatile matter of the positive electrode mixture is preferably 1 to 20 mass %, more preferably 1.5 to 10 mass %, from the viewpoint of improving the output characteristics and electrical characteristics of the lithium ion secondary battery.
[0060] Examples of the binder include fluororesins such as polyvinylidene fluoride and polytetrafluoroethylene; synthetic rubbers such as styrene-butadiene rubber and nitrile butadiene rubber; polyamide resins such as polyamideimide; polyolefin resins such as polyethylene and polypropylene; poly(meth)acrylic resins; polyacrylic acid; cellulose resins such as carboxymethylcellulose; and the like. Each of the binders may be used alone or in combination of two or more. The binder may be dissolved in a solvent or dispersed in a solvent when used.
[0061] Examples of the solvent include N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, methyl ethyl ketone, tetrahydrofuran, acetonitrile, acetone, ethanol, ethyl acetate, water, etc. The solvent may be used alone or in combination of two or more. The amount of the solvent used is not particularly limited and may be appropriately determined depending on the production method and the materials used.
[0062] The positive electrode mixture may contain, as other components as necessary, for example, non-fluorinated polymers such as (meth)acrylic polymers, nitrile polymers, and diene polymers, fluorinated polymers such as polytetrafluoroethylene, and other polymers; emulsifiers such as anionic emulsifiers, nonionic emulsifiers, and cationic emulsifiers; dispersants such as styrene-maleic acid copolymers and polymer dispersants such as polyvinylpyrrolidone; thickeners such as carboxymethylcellulose, hydroxyethylcellulose, polyvinyl alcohol, polyacrylic acid (salt), and alkali-soluble (meth)acrylic acid-(meth)acrylic acid ester copolymers; preservatives, etc. The content of other components in the non-volatile content of the positive electrode mixture is preferably 0 to 15% by mass, more preferably 0 to 10% by mass.
[0063] The positive electrode mixture can be prepared, for example, by mixing a positive electrode active material, a conductive assistant, a binder, a solvent, and other components as necessary, and dispersing the mixture using a bead mill, a ball mill, an agitator mixer, or the like.
[0064] The method for forming the positive electrode (coating method) is not particularly limited, and examples thereof include (1) a method in which a positive electrode composite is coated (and dried) on a positive electrode current collector by a conventional coating method (e.g., a doctor blade method, etc.), (2) a method in which a positive electrode current collector is immersed in a positive electrode composite (and dried), (3) a method in which a sheet formed of a positive electrode composite is bonded (e.g., bonded via a conductive adhesive) to a positive electrode current collector and pressed (and dried), (4) a method in which a positive electrode composite to which a liquid lubricant has been added is coated or cast on a positive electrode current collector, formed into a desired shape, and then the liquid lubricant is removed (and then stretched in a uniaxial or multiaxial direction), and (5) a method in which a positive electrode composite (or a solid content forming a positive electrode composite layer) is slurried with an electrolyte, transferred in a semi-solid state to a current collector (positive electrode current collector), and used as an electrode (positive electrode) without drying.
[0065] Incidentally, the positive electrode mixture layer may be dried or pressed after being formed or coated (applied), as necessary.
[0066] (Negative electrode) The negative electrode includes a negative electrode current collector and a negative electrode mixture layer, and the negative electrode mixture layer is formed on the negative electrode current collector and is usually formed into a sheet shape.
[0067] Examples of metals used for the negative electrode current collector include iron, copper, aluminum, nickel, stainless steel (SUS), titanium, tantalum, gold, platinum, etc. Among these, copper is preferred. The shape and dimensions of the negative electrode current collector are not particularly limited.
[0068] The negative electrode mixture layer is formed from a negative electrode mixture (negative electrode composition) that contains a negative electrode active material, a conductive assistant, a binder, a solvent for dispersing these components, and the like.
[0069] The negative electrode active material may be any of the conventionally known negative electrode active materials used in various batteries (e.g., lithium secondary batteries) and the like, as long as it can absorb and release various ions (e.g., lithium ions). Specific negative electrode active materials include graphite materials such as artificial graphite and natural graphite, mesophase sintered bodies made from coal and petroleum pitch, carbon materials such as non-graphitizable carbon, Si-based negative electrode materials such as Si, Si alloys, and SiO (silicon oxide), Sn-based negative electrode materials such as Sn alloys, lithium metal, and lithium alloys such as lithium-aluminum alloys. The negative electrode active materials may be used alone or in combination of two or more. For example, a composite material of silicon oxide and graphite may be used.
[0070] The negative electrode mixture may further contain a conductive assistant (conductive substance), a binder, a solvent, etc. The conductive assistant, binder, solvent, etc. may be the same as those described above. The proportions of the conductive assistant, binder, solvent, etc. may also be the same as those described above.
[0071] The negative electrode may be produced by the same method as the positive electrode.
[0072] (Separator) The secondary battery may include a separator. The separator is disposed so as to separate the positive electrode from the negative electrode. There is no particular limitation on the separator, and any conventionally known separator may be used in the present disclosure. Specific examples of the separator include porous sheets made of polymers capable of absorbing and retaining an electrolyte (non-aqueous electrolyte) (e.g., polyolefin-based microporous separators, cellulose-based separators, etc.), nonwoven fabric separators, porous metal bodies, etc.
[0073] Examples of the material for the porous sheet include polyethylene, polypropylene, and a laminate having a three-layer structure of polypropylene / polyethylene / polypropylene.
[0074] Examples of materials for the nonwoven fabric separator include cotton, rayon, acetate, nylon, polyester, polypropylene, polyethylene, polyimide, aramid, glass, etc., and depending on the required mechanical strength, etc., the above-mentioned materials may be used alone or in combination of two or more types.
[0075] Also, a separator having inorganic particles applied to at least one surface (one side) can be suitably used. In other words, a separator having an insulating layer containing inorganic particles on at least one surface is preferred. By using a separator having an insulating layer, the synergistic effect of the combination of the compounds (1) to (3) is further improved. When an insulating layer is formed on one surface of the separator, the surface having the insulating layer may be disposed on the positive electrode side or the negative electrode side. Among separators having an insulating layer on at least one surface, a separator having an insulating layer formed on both sides is preferred.
[0076] The insulating layer is made of an insulating mixture containing inorganic particles, a binder, a solvent for dispersing these components, and the like.
[0077] Inorganic particles include alumina, silica, magnesia, titania, zirconia, and LiNbO 3 , LIPON (Li 3+y PO 4-x Nx ), LISICON (Lithium-Super-Ion-CONductor), Thio-LISICON (e.g. Li 3.25 Ge 0.25 P 0.75 S 4 ), Li 2 S alone or Li 2 SP 2 S 5 , Li 2 S-SiS 2 , Li 2 S-GeS 2 , Li 2 S.B. 2 S 5 , Li 2 S-Al 2 S 5 , Li 2 O-Al 2 O 3 -TiO 2 -P 2 O 5 Examples of the ceramic particles include those made of ceramics such as LATP.
[0078] The binder may be the same as the binder described above, for example, a polymer compound such as polyvinylidene fluoride (PVdF), etc. The solvent may be the same as that used for the positive and negative electrodes, for example, N-methyl-2-pyrrolidone (NMP), etc.
[0079] The insulating layer may be formed (applied) in the same manner as the positive electrode forming method (applied) described above. In this case, the positive electrode composite material is replaced with an insulating composite material, the positive electrode current collector is replaced with a separator, and an insulating layer is formed on one or both sides of the separator.
[0080] (Battery exterior materials) A battery element including a positive electrode, a negative electrode, and a non-aqueous electrolyte (and further a separator) is usually housed in a battery exterior material to protect the battery element from external impacts, environmental deterioration, etc., during use of the battery. There are no particular limitations on the material of the battery exterior material, and any of the conventionally known exterior materials can be used.
[0081] If necessary, the battery exterior material may contain expanded metal, an overcurrent protection element such as a fuse or a PTC element, lead plates, etc. to prevent pressure rise inside the battery and overcharging and discharging.
[0082] The shape of the battery (lithium ion secondary battery, etc.) is not particularly limited, and any shape conventionally known as the shape of a battery (lithium ion secondary battery, etc.) can be used, such as a cylindrical shape, a square shape, a laminated shape, a coin shape, a large shape, etc. In addition, when used as a high-voltage power source (several tens of volts to several hundreds of volts) to be mounted on an electric vehicle, a hybrid electric vehicle, etc., it can also be made into a battery module composed of individual batteries connected in series.
[0083] The rated charging voltage of a secondary battery (lithium ion secondary battery, etc.) is not particularly limited, but when the secondary battery has a positive electrode containing the above-mentioned ternary positive electrode active material as a main component, it may be 3.6 V or more, preferably 4.0 V or more, more preferably 4.1 V or more, and further preferably 4.2 V or more. The higher the rated charging voltage, the higher the energy density can be, but from the viewpoint of safety, etc., the rated charging voltage may be 4.6 V or less (for example, 4.5 V or less), etc.
[0084] <Secondary battery manufacturing method> The secondary battery according to this embodiment can be easily manufactured, for example, by stacking a positive electrode and a negative electrode (with a separator interposed between them as necessary), placing the resulting laminate in a battery exterior material, injecting a nonaqueous electrolyte into the battery exterior material, and sealing it.
[0085] <Effects> The nonaqueous electrolyte and the secondary battery according to this embodiment have the following advantages. The nonaqueous electrolyte according to the present embodiment contains three specific components: a sulfonylimide compound (1), a fluorophosphate compound (2), and a complex compound (3). As a result, a battery using this nonaqueous electrolyte can improve the charging characteristics at low temperatures and suppress self-discharge, which is a problem specific to nonaqueous electrolytes containing the sulfonylimide compound (1), particularly self-discharge after storage at high temperatures. The non-aqueous electrolyte according to this embodiment can further improve the above-mentioned effects by using four specific components that further include a fluorine-containing carbonate compound. A battery including a separator having an insulating layer containing inorganic particles on at least one surface thereof together with the nonaqueous electrolyte according to this embodiment can further improve the above-mentioned effects. EXAMPLES
[0086] The present disclosure will be described below based on examples. Note that the present disclosure is not limited to the following examples, and the following examples can be modified or changed based on the spirit of the present disclosure, and are not excluded from the scope of the present disclosure.
[0087] <Example 1 Series> (Production Example 1) Under an argon atmosphere, 10 mL of diethyl ether and 0.75 g of lithium oxide were added to a 100 mL Erlenmeyer flask to prepare a mixed solution, which was then cooled to 0° C. with stirring. 10.5 g of boron trifluoride diethyl ether complex was added to the mixed solution over 30 minutes with stirring to prepare a reaction solution, which was then kept at 25° C. and stirred for 16 hours. The reaction solution was then filtered, and the lithium oxide / 2BF 3 A crude complex was obtained. The resulting lithium oxide / 2BF 3 The crude complex was washed three times with 10 mL of dibutyl ether to remove excess boron trifluoride diethyl ether complex. The solid obtained was dried under reduced pressure at 110°C for 10 hours to obtain a solid solution of lithium oxide and 2BF 3 The complex "(LiBF 3 ) 2 O" 4.04g was obtained.
[0088] (Production Example 2) Lithium oxide / BF was prepared in the same manner as in Production Example 1, except that 3.55 g of boron trifluoride diethyl ether complex was used instead of 10.5 g of boron trifluoride diethyl ether complex. 3 The complex LiBF 3 2.24 g of "OLi" was obtained.
[0089] (Examples 1-1 to 1-56) [Preparation of non-aqueous electrolyte] The electrolyte solvent was a mixed solvent of ethylene carbonate (EC):ethyl methyl carbonate (EMC) = 3:7 (volume ratio) (Kishida Chemical Co., Ltd., the same below), and the sulfonylimide compound (1) was LiFSI (Nippon Shokubai Co., Ltd., the same below) and the fluorophosphate compound (2) were LiPF 6 (manufactured by Stella Chemifa Corporation, the same applies below) was dissolved in the solution to the concentrations shown in Tables 1-1 and 1-2. The complex compound (3) obtained in Production Example 1 (LiBF 3 ) 2 O was added so as to obtain the contents shown in Tables 1-1 and 1-2, and the mixture was stirred for one day to prepare a nonaqueous electrolyte solution (hereinafter, simply referred to as electrolyte solution).
[0090] (Comparative Example 1-1) The solution obtained above was diluted with (LiBF 3 ) 2 A nonaqueous electrolyte solution was prepared in the same manner as in each of the Examples, except that no O was added. That is, in Comparative Example 1-1, the solution obtained above was used as the nonaqueous electrolyte solution.
[0091] (Comparative Example 1-2) LiPF 6 A non-aqueous electrolyte solution was prepared in the same manner as in each of the Examples, except that an electrolyte salt having a simple salt composition containing only zinc was used.
[0092] (Comparative Example 1-3) A non-aqueous electrolyte solution was prepared in the same manner as in each of the Examples, except that an electrolyte salt having a simple salt composition containing only LiFSI was used.
[0093] [Making laminated batteries] (Preparation of positive electrode) LiNi, a ternary positive electrode active material 1 / 3 Co 1 / 3 Mn 1 / 3 O 2(manufactured by Umicore, product number: MX7h), acetylene black (AB, manufactured by Denka Co., Ltd., product name: Denka Black (registered trademark)), graphite (manufactured by Nippon Graphite Industries Co., Ltd., product number: SP270), and polyvinylidene fluoride (PVdF, manufactured by Kureha Co., Ltd., product number: KF1120) were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode mixture slurry (positive electrode active material: AB: graphite: PVdF = 93: 2: 2: 3 (solid content mass ratio)). Next, the obtained positive electrode mixture slurry was applied to an aluminum foil (positive electrode current collector, manufactured by Nippon Foil Co., Ltd., thickness 15 μm) so that the coating weight after drying was 19.4 mg / cm 2 The mixture was then dried on a hot plate at 110°C for 10 minutes, and then dried in a vacuum drying oven at 110°C for 12 hours. Thereafter, the mixture was pressed with a roll press to a density of 3.1 g / cm. 3 The mixture was pressed until a sheet-like positive electrode (thickness: 83 μm) was obtained.
[0094] (Preparation of negative electrode) Graphite (natural graphite (Hitachi Chemical Co., Ltd., product number: SMG): artificial graphite (TIMCAL, product number: SFG15) = 85:15 (solid content mass ratio)) as a negative electrode active material, styrene-butadiene rubber (SBR, binder), and carboxymethyl cellulose (CMC, binder) were dispersed in ultrapure water to prepare a negative electrode composite slurry (negative electrode active material: SBR: CMC = 97.3: 1.5: 1.2 (solid content mass ratio)). The obtained negative electrode composite slurry was then applied to a copper foil (negative electrode current collector, Fukuda Metal Foil and Powder Co., Ltd., thickness 15 μm) so that the coating weight after drying was 9.8 mg / cm. 2 The mixture was then dried on a hot plate at 80°C for 10 minutes, and then dried in a vacuum drying oven at 100°C for 12 hours. Thereafter, the mixture was pressed with a roll press to a density of 1.3 g / cm. 3 The mixture was pressed until a sheet-like negative electrode (thickness: 113 μm) was obtained.
[0095] (Making laminated batteries) The obtained positive and negative electrodes were cut, the polarity leads were ultrasonically welded, the positive and negative electrodes were placed opposite each other via a 20 μm polyethylene (PE) separator, and the three sides were sealed with a laminate exterior to prepare a non-injected battery. Next, 700 μL of each electrolyte solution shown in Tables 1-1 and 1-2 was added to one of the unsealed sides of the non-injected battery.
[0096] After the electrolyte injection, the battery was precharged at 0.2C (6mA) for 2 hours in an unsealed state. The battery was then vacuum sealed and left at room temperature for 3 days. After 3 days, it was charged at 0.5C (15mA) for 5 hours at 4.2V, followed by charging and discharging at 0.2C (6mA) with a termination at 2.75V. One piece of the laminate was opened and the battery was vacuum sealed again to release the gas. The battery after the gas release was charged and discharged under the following conditions, and this operation was called the conditioning process. As a result of the above, a 4.2V laminate battery (cell) with a capacity of 30mAh was produced. (Conditioning conditions) Charge: 0.5C (15mA), 4.2V for 5 hours (25℃) ⇒ Discharge: 1C (30mA), terminate at 2.75V (25℃).
[0097] [Battery evaluation] Using the cells after the conditioning process, the charging time at low temperature and the self-discharge after storage at high temperature were evaluated. The results are shown in Tables 1-1 and 1-2.
[0098] (Charging time at low temperatures) The charging time (min) was determined when the cell after the conditioning step was charged at a constant current of 4.2 V, 1 C (30 mA) at −20° C. Note that a longer charging time indicates better charging characteristics.
[0099] (self-discharge) The cell after the conditioning step was charged at a constant current and constant voltage of 1C (30mA) at room temperature, terminated at 0.02C (0.6mA) at 4.2V, and fully charged (SOC 100%). The fully charged cell was stored at 60°C for 4 weeks. After cooling the cell at room temperature for 3 hours after storage, the open circuit voltage (OCV) of the cell was measured at room temperature, and this measurement value was taken as the "OCV after storage". Note that the larger the "OCV after storage" value, the smaller the self-discharge from the fully charged state, meaning that the self-discharge of the battery is suppressed.
[0100] [Table 1-1]
[0101] [Table 1-2]
[0102] From the results in Tables 1-1 and 1-2, LiFSI, LiPF 6 and (LiBF 3 ) 2 It was found that the batteries using the nonaqueous electrolytes of the Examples, which contain the three components LiFSI, LiBF, and O, have a longer charge time at low temperatures and suppress self-discharge after high-temperature storage, compared to the batteries using the nonaqueous electrolytes of the Comparative Examples, which contain only two components without any one of the components. 3 ) 2 The battery using the nonaqueous electrolyte of Comparative Example 1-3 containing only the two components O could not be charged normally and could not function as a battery.
[0103] <Example 2 Series> (Examples 2-1 to 2-56, Comparative Examples 2-1 to 2-3) Complex compound (3) (LiBF 3 ) 2 Instead of O, LiBF obtained in Production Example 2 3 A non-aqueous electrolyte solution was prepared in the same manner as in Example 1 except that OLi was used. 6 Concentration of LiBF3 The content of OLi is shown in Tables 2-1 and 2-2. Using each of the obtained nonaqueous electrolyte solutions, laminate batteries (cells) were produced and the batteries were evaluated in the same manner as in Example 1. The results are shown in Tables 2-1 and 2-2.
[0104] [Table 2-1]
[0105] [Table 2-2]
[0106] From the results in Tables 2-1 and 2-2, as in the Example 1 series, LiFSI, LiPF 6 and LiBF 3 It was found that the batteries using the nonaqueous electrolytes of the Examples containing the three components LiFSI, LiBF, and OLi had a longer charge time at low temperatures and suppressed self-discharge after high-temperature storage compared to the batteries using the nonaqueous electrolytes of the Comparative Examples containing only two components without any one of the components. 3 The battery using the nonaqueous electrolyte of Comparative Example 2-3 containing only the two components OLi could not be charged normally and could not function as a battery.
[0107] <Example 3 Series> (Examples 3-1 to 3-10, Comparative Examples 3-1 to 3-5) [Preparation of non-aqueous electrolyte] A non-aqueous electrolyte solution was prepared in the same manner as in Examples 1 and 2. The concentrations of LiFSI and LiPF 6 The concentration of and the type and content of complex compound (3) are shown in Table 3.
[0108] [Preparation of laminated battery and evaluation of the battery] Except for using an alumina-coated polyethylene separator, in which alumina particles were applied to both sides of the polyethylene separator, instead of the 20 μm polyethylene (PE) separator, a 4.2 V, 30 mAh capacity laminate battery (cell) was fabricated in the same manner as in Examples 1 and 2, and the battery was evaluated. The results are shown in Table 3.
[0109] The alumina-coated polyethylene separator was produced by the following method. First, 80 parts by mass of alumina particle powder with an average particle size of 0.5 μm as inorganic particles and 20 parts by mass of polyvinylidene fluoride (PVdF) as a binder were mixed and diluted with N-methyl-2-pyrrolidone (NMP) to prepare a mixed solution. A 20 μm polyethylene sheet was immersed in the resulting mixed solution, the film thickness was controlled with a gravure roller, and the sheet was passed through a dryer at 120° C. to remove the solvent, thereby producing an alumina-coated polyethylene separator in which both sides of the sheet were coated with a 5 μm-thick alumina-containing porous film.
[0110] [Table 3]
[0111] From the results in Table 3, Examples 3-3 and 3-8 in which the same nonaqueous electrolyte was used implementation Example 3- 11 ,3- 12 In comparison with the batteries with alumina-coated polyethylene separators (Examples 3-3 and 3-8), the batteries with polyethylene separators not coated with alumina particles ( implementation Example 3- 11 ,3- 12 ), the charging time at low temperatures is longer and self-discharge after high-temperature storage is suppressed. 6 , and (LiBF 3 ) 2 O or LiBF 3 The improvement effect of the specific combination of three components, OLi, can be further enhanced.
[0112] <Example 4 Series> The nonaqueous electrolyte solutions were prepared in the same manner as in Examples 1 and 2, except that fluoroethylene carbonate (FEC) was further added as an additive to the nonaqueous electrolyte solution to the content shown in Table 4. The concentration of LiFSI, LiPF 6 The concentration of, the type and content of complex compound (3), and the content of FEC are shown in Table 4. Using each of the obtained nonaqueous electrolyte solutions, laminate batteries (cells) were produced in the same manner as in Example 1 series, and the batteries were evaluated. The results are shown in Table 4.
[0113] [Table 4]
[0114] From the results in Table 4, Examples 4-3 and 4-8, implementation Example 4- 11 ,4- 12 In comparison with the batteries using a non-aqueous electrolyte containing fluoroethylene carbonate (FEC) (Examples 4-3 and 4-8), the batteries using a non-aqueous electrolyte containing FEC ( implementation Example 4- 11 ,4- 12 ), the charging time at low temperatures is longer and the self-discharge after high-temperature storage is suppressed. 6 , (LiBF 3 ) 2 O or LiBF 3 The improvement effect achieved by the combination of the specific three components can be further enhanced by the combination of the specific four components, OLi and FEC.
[0115] <Example 5 Series> (Examples 5-1 to 5-56, Comparative Examples 5-1 to 5-3) [Preparation of non-aqueous electrolyte] A non-aqueous electrolyte solution was prepared in the same manner as in Example 1. 6and the complex compound (3) obtained in Production Example 1 (LiBF 3 ) 2 The O content is shown in Tables 5-1 and 5-2.
[0116] [Making laminated batteries] (Preparation of positive electrode) LiNi, a ternary positive electrode active material 0.8 Co 0.1 Mn 0.1 O 2 (Beijing Diabe), acetylene black (AB, Denka Co., Ltd., product name: Denka Black (registered trademark)), graphite (Nippon Graphite Industries Co., Ltd., product number: SP270), and polyvinylidene fluoride (PVdF, Kureha Co., Ltd., product number: KF1120) were dispersed in N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode mixture slurry (positive electrode active material: AB: graphite: PVdF = 93: 3: 3: 3 (solid content mass ratio)). Next, the obtained positive electrode mixture slurry was applied to an aluminum foil (positive electrode current collector, Nippon Foil Co., Ltd., thickness 15 μm) so that the coating weight after drying was 19.4 mg / cm. 2 The mixture was then dried on a hot plate at 110°C for 10 minutes, and then dried in a vacuum drying oven at 110°C for 12 hours. Thereafter, the mixture was pressed with a roll press to a density of 3.1 g / cm. 3 The mixture was pressed until a sheet-like positive electrode (thickness: 78 μm) was obtained.
[0117] (Preparation of negative electrode) A silicon oxide (SiO) / graphite composite material (manufactured by BTR, product number: BSO-600) as a negative electrode active material, a conductive assistant (manufactured by Showa Denko K.K., product number: VGCF-H (registered trademark) and (manufactured by Imerys, product number: Super-P (registered trademark), styrene-butadiene rubber (SBR, binder) and carboxymethyl cellulose (CMC, binder) were dispersed in ultrapure water to prepare a negative electrode mixture slurry (negative electrode active material: VGCF:Super-P:SBR:CMC = 90:2:3:3:2 (solid content mass ratio)). The obtained negative electrode mixture slurry was then applied to a copper foil (negative electrode current collector, manufactured by Fukuda Metal Foil and Powder Co., Ltd., thickness 15 μm) so that the coating weight after drying was 6.8 mg / cm.2 The mixture was then dried on a hot plate at 80°C for 10 minutes, and then dried in a vacuum drying oven at 100°C for 12 hours. Thereafter, the mixture was pressed with a roll press to a density of 1.3 g / cm. 3 The mixture was pressed until a sheet-like negative electrode (thickness: 64 μm) was obtained.
[0118] (Making laminated batteries) Except for using the positive and negative electrodes obtained above, a laminate battery (cell) of 4.2 V and capacity of 30 mAh was produced in the same manner as in Example 1 series, and the battery was evaluated. The results are shown in Tables 5-1 and 5-2.
[0119] [Table 5-1]
[0120] [Table 5-2]
[0121] The results in Tables 5-1 and 5-2 show that the same effects as those in the Example 1 series can be obtained even in batteries in which the positive electrode active material and the negative electrode active material are changed and a positive electrode and a negative electrode are combined in a manner different from that in the Example 1 series.
[0122] <Example 6 Series> (Examples 6-1 to 6-56, Comparative Examples 6-1 to 6-3) Complex compound (3) (LiBF 3 ) 2 Instead of O, LiBF obtained in Production Example 2 3 A non-aqueous electrolyte solution was prepared in the same manner as in Example 1 except that OLi was used. 6 Concentration of LiBF 3 The content of OLi is shown in Tables 6-1 and 6-2. Using each of the obtained nonaqueous electrolytes, laminate batteries (cells) were produced in the same manner as in Example 5 series, and the batteries were evaluated. The results are shown in Tables 6-1 and 6-2.
[0123] [Table 6-1]
[0124] [Table 6-2]
[0125] The results in Tables 6-1 and 6-2 show that the same effects as those in the Example 2 series can be obtained even in batteries in which the positive electrode active material and the negative electrode active material are changed and a positive electrode and a negative electrode are combined in a manner different from that in the Example 2 series. [Industrial Applicability]
[0126] As described above, the present disclosure is suitable for nonaqueous electrolyte solutions used in lithium ion secondary batteries.
Claims
1. A non-aqueous electrolyte solution containing a compound represented by any one of general formulas (1) to (3). LiN (R 1 SO 2 ) (R 2 SO 2 ) (R 1 and R 2 are the same or different and represent a fluorine atom, an alkyl group having 1 to 6 carbon atoms, or a fluoroalkyl group having 1 to 6 carbon atoms.) (1) LiPF a (C m F 2m+1 ) 6-a (a:0≦a≦6、m:1≦m≦4) (2) (Li) m (A) n (U.F. x ) y (A represents an oxygen atom, a sulfur atom, a phosphorus atom, or a nitrogen atom, and U represents a boron atom or a phosphorus atom; m: 1≦m≦6, n: 1≦n≦6, x: 3 or 5, and y: 1≦y≦6) (3)
2. The compound represented by the general formula (3) is (LiBF 3 ) 2 O and LiBF 3 The nonaqueous electrolyte according to claim 1 , comprising at least one of OLi.
3. The nonaqueous electrolyte according to claim 1 or 2, wherein the content of the compound represented by the general formula (3) is 0.01% by mass or more and 20% by mass or less.
4. The compound represented by the general formula (1) is LiN(FSO 2 ) 2 The non-aqueous electrolyte according to any one of claims 1 to 3, comprising:
5. The nonaqueous electrolyte according to any one of claims 1 to 4, wherein the molar ratio of the compound represented by the general formula (1) to the compound represented by the general formula (2) is 1:25 or more and 5:1 or less.
6. The nonaqueous electrolyte according to any one of claims 1 to 4, wherein the molar ratio of the compound represented by the general formula (1) to the compound represented by the general formula (2) is 1:120 or more and 1:25 or less.
7. The molar ratio of the concentration of the compound represented by the general formula (1) to the concentration of the compound represented by the general formula (2) is 5:1 or more and 12:1 or less. The nonaqueous electrolyte solution according to any one of claims 1 to 4.
8. The molar ratio of the compound concentration represented by the general formula (1) to the compound concentration represented by the general formula (2) is 1:120 or more and 12:1 or less. The nonaqueous electrolyte solution according to any one of claims 1 to 4.
9. The nonaqueous electrolyte according to any one of claims 1 to 8, further comprising a fluorine-containing carbonate compound.
10. A secondary battery comprising the nonaqueous electrolyte according to any one of claims 1 to 9.
11. The secondary battery according to claim 10 , further comprising a separator having at least one surface coated with inorganic particles.
Citation Information
Patent Citations
Battery and its electrolyte
JP1997022706A
Electrolyte for power storage device and nonaqueous electrolyte solution
JP2019169302A
Battery
JP2020004598A
Electrolyte for power storage devices and nonaqueous electrolyte solution
WO2019180945A1